The Fortification of Sunflower oil with Oryzanol and its effect on Chemical Characteristics - Ali W Nofan; Ethar Z Naji (Tikrit Journal of Pure Science)
Sunflower oil was fortified with the anti-oxidant oryzanol .The supported samples were placed inside a socket at 120 ° C and   the results showed a decrease in iodine number (131, 130, 129, 127) and an increase in the acidity number (0.22, 0.24, 0.27, 0.30), and the peroxide number showed an increase (2.37, 2.42. , 2.46, 2.51), and the results also showed an increase in the percentage of free fatty acids (0.08, 0.08, 0.09, 0.10)% as well as an increase in saponification number (190, 192, 197, 200).